2015
DOI: 10.1097/shk.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Protects Against Hemorrhagic Shock and Resuscitation–Induced Microcirculatory Injury and Tissue Injury

Abstract: Traumatic injury is a significant cause of morbidity and mortality worldwide. Microcirculatory activation and injury from hemorrhage contributes to organ injury. Many adaptive responses occur within the microcirculatory beds to limit injury including up regulation of heme oxygenase (HO) enzymes, the rate limiting enzymes in the breakdown of heme to carbon monoxide (CO), iron, and biliverdin. Here we tested the hypothesis that CO abrogates trauma induced injury and inflammation protecting the microcirculatory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…vasodilation, anti-inflammatory actions, modulation of cGMP signalling, etc.) (Peers et al 2015;Peers and Lefer 2011;Nassour et al 2015;Munoz-Sanchez and Chanez-Cardenas 2014), it is possible that some of the observed effects of GYY4137 could also be due, at least in part, to a contribution by CO. This may be especially important given the inefficient manner in H 2 S generated from GYY4137 necessitates the use of high concentrations/doses of this compound to elicit pharmacological responses in cells, tissues and whole animals (see Table 1).…”
Section: Gyy4137mentioning
confidence: 92%
“…vasodilation, anti-inflammatory actions, modulation of cGMP signalling, etc.) (Peers et al 2015;Peers and Lefer 2011;Nassour et al 2015;Munoz-Sanchez and Chanez-Cardenas 2014), it is possible that some of the observed effects of GYY4137 could also be due, at least in part, to a contribution by CO. This may be especially important given the inefficient manner in H 2 S generated from GYY4137 necessitates the use of high concentrations/doses of this compound to elicit pharmacological responses in cells, tissues and whole animals (see Table 1).…”
Section: Gyy4137mentioning
confidence: 92%
“…It should be noted that commercial preparations of GYY4137 are sold as a dichloromethane complex, and it has been reported that dichloromethane is metabolized to carbon monoxide (CO) [304, 305] an important gasotransmitter. Since CO is reported to have similar biological effects as H 2 S [306308], it is possible that some of the observed effects of GYY4137 could also be due, at least in part, to a contribution by CO [289]. …”
Section: Modulation Of H2s Levels As a Strategy To Treat Cancermentioning
confidence: 99%
“…Intravital microscopy of hepatic tissue clearly shows vasodilatory effects in capillary beds without affecting central pressures. 111 Whether a similar phenomenon occurs in the lung and heart remains to be studied. In all likelihood all are valid explanations towards understanding how HO-1/CO influences vessel remodeling and that collectively each contributes towards the maintenance and restoration of normal pulmonary artery and right heart function.…”
Section: Ho-1 and Cardiovascular Protectionmentioning
confidence: 99%
“…These data suggest different regulatory mechanisms at work that are cGMP independent. 111 The reports described above would suggest that HO-1 and CO act in a manner that befits the needs of the tissue and restricting their function to one cellular process or another such as anti-apoptotic or anti-inflammatory does not fully and accurately define their role in pathological settings. Induction of HO-1 and CO generation provides the cell, and organism with the optimal chance at maintaining function to ensure survival.…”
Section: Ho-1 and Cardiovascular Protectionmentioning
confidence: 99%